A general asymmetric copper-catalysed Sonogashira C(sp3)–C(sp) coupling - Dong, Xiao-Yang; Zhang, Yu-Feng; Ma, Can-Liang; Gu, Qiang-Shuai; Wang, Fu-Li; Li, Zhong-Liang; Jiang, Sheng-Peng; Liu, Xin-Yuan (Nature chemistry, 2019)
Continued development of the Sonogashira coupling has made it a well established and versatile reaction for the straightforward formation of C–C bonds, forging the carbon skeletons of broadly useful functionalized molecules. However, asymmetric Sonogashira coupling, particularly for C( sp 3 )–C( sp ) bond formation, has remained largely unexplored. Here we demonstrate a general stereoconvergent Sonogashira C( sp 3 )–C( sp ) cross-coupling of a broad range of terminal alkynes and racemic alkyl halides (>120 examples) that are enabled by copper-catalysed radical-involved alkynylation using a chiral cinchona alkaloid-based P,N-ligand. Industrially relevant acetylene and propyne are successfully incorporated, laying the foundation for scalable and economic synthetic applications. The potential utility of this method is demonstrated in the facile synthesis of stereoenriched bioactive or functional molecule derivatives, medicinal compounds and natural products that feature a range of chiral C( sp 3 )–C( sp / sp 2 / sp 3 ) bonds. This work emphasizes the importance of radical species for developing enantioconvergent transformations. Asymmetric Sonogashira C( sp 3 )–C( sp ) couplings provide complementary approaches to established C( sp 3 )–C( sp 2 / sp 3 ) couplings for chiral C–C bond formation; however, relatively few reactions have been developed. Now, a versatile, enantioconvergent Sonogashira coupling via a radical intermediate has been developed. The approach uses a copper catalyst featuring a multidentate electron-rich cinchona alkaloid-derived ligand.